2023
DOI: 10.1093/pnasnexus/pgad389
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic synthesis of mineral-bearing microdroplet from inorganic carbon photoreduction at air–water interface

Qiuyue Ge,
Yangyang Liu,
Wenbo You
et al.

Abstract: The origin of life on Earth is an enigmatic and intricate conundrum that has yet to be comprehensively resolved despite recent significant developments within the discipline of archaeology and geology. Chemically, metal-sulfide minerals are speculated to serve as an important medium for giving birth in early life while yet so far direct evidence to support the hypothesis for the highly efficient conversion of inorganic carbon into praxiological biomolecules remains scarce. Here, we in this study, for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Ge et al. has also demonstrated that the gas‐liquid interface of microdroplets significantly accelerates photocatalytic CO 2 reduction reactions [29,30] …”
Section: Methodsmentioning
confidence: 99%
“…Ge et al. has also demonstrated that the gas‐liquid interface of microdroplets significantly accelerates photocatalytic CO 2 reduction reactions [29,30] …”
Section: Methodsmentioning
confidence: 99%
“…1,000 ppmv by the end of the 21st century, leaving this trace gas even more potentially important in atmospheric relevant reaction (Xia et al, 2021). Despite the inactive chemical properties of this gas in the ambient environment, our group's recent study highlighted the key role of CO 2 in atmospherically photochemical processes and producing carbonate radical ions upon solar irradiation and participating in subsequent fast SO 2 oxidation, and reaction schemes are complicated by different authentic mineral dust particles and dust proxies (Deng et al, 2020;Ge et al, 2023;. Carbonate radical ions also show distinct effects on SO 2 oxidation rates and reaction channels in dark and light control experiments in specific meteorological conditions (e.g., low RH and weak light intensity).…”
mentioning
confidence: 99%